2008
DOI: 10.1097/id.0b013e318166d88b
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Comparison of Prosthetic Complications of Implant-Supported Overdentures With Different Attachment Systems

Abstract: Implant-supported overdentures with bar or ball attachments may be considered to be reliable methods in the treatment of the edentulous individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 16 publications
1
50
0
9
Order By: Relevance
“…Several studies have been reported the evaluation of the ball and bar attachment systems. (7,9,10,16) On the other hand, there is a lack of clinical study which investigate the Locator attachment system. (15) The present study evaluated the comparison of the bar, ball and Locator attachment system with regard to a clinical point of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been reported the evaluation of the ball and bar attachment systems. (7,9,10,16) On the other hand, there is a lack of clinical study which investigate the Locator attachment system. (15) The present study evaluated the comparison of the bar, ball and Locator attachment system with regard to a clinical point of view.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8,9) Many clinical studies evaluated the use of the bar and ball attachments in terms of various clinical parameters. (9,10,11) The Locator attachment (Zest Anchors, Inc, homepage, Escondido, CA, USA) which was introduced in 2001, is a new system, which does not use the splinting of implants. This attachment is self-aligning and has dual retention and in different colors with different retention values.…”
Section: Introductionmentioning
confidence: 99%
“…All the studies were published from 2000-2017. In nineteen studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) the implants were placed by means of a standard surgical protocol in a healed normal implant site of bone Type III or IV. an ‗early' implant placement in two studies (Type II) was performed and immediate implant placement in other three studies (Type I) was done.…”
Section: Results:-mentioning
confidence: 99%
“…The longevity of implant-supported dental prostheses is obtained by stability, passive fit of prosthetic infrastructures on the implant connections [1][2][3]. The absence of satisfactory fit induces the irregular distribution of masticatory loads, resulting in deformation of the adjacent bone tissue3 and of the prosthetic components [4][5], compromising the therapeutic success of the implant and its components [6].…”
Section: Introductionmentioning
confidence: 99%